Математическое моделирование электростатических полей в кусочно-однородных телах сложной формы методом R-функций - Максименко-Шейко, К.В. (Электронное моделирование, 2009)
Two techniques of the account of joining conditions arising in bodies, consisting of parts with various physical characteristics, with the use of the R-functions theory are considered in the paper. The preference is given to the technique rather based on representation of structures of solutions by various analytical expressions in various subareas, than on special transformations of coordinates. Numerical results are given.